Endovenous Laser Ablation of Varicose Veins Preserves Biological Properties of Vascular Endothelium and Modulates Proinflammatory Agent Profile More Favorably Than Classic Vein Stripping. (20th February 2017) - Uruski, Paweł; Aniukiewicz, Krzysztof; Mikuła-Pietrasik, Justyna; Sosińska, Patrycja; Tykarski, Andrzej; Książek, Krzysztof; Krasiński, Zbigniew
Abstract : Here we compared effect of serum from varicose patients undergoing endovenous laser ablation (EVLA) and classic vein stripping (CVS) on biological properties of endothelial cells and on the local and systemic profiles of proinflammatory agents. Results showed that serum from EVLA patients improved proliferation and reduced senescence and oxidative stress in the endothelial cells, as compared with the serum from CVS patients. These effects were related to a suppressed activity of TGF- β 1, the level of which in the serum from the EVLA patients was decreased. Medium generated by the cells subjected to EVLA serum contained decreased amounts of ICAM-1, VCAM-1, and E-selectin and increased amount of uPA, whereas the serum itself contained decreased concentrations of ICAM-1, E-selectin, and P-selectin and increased concentrations of uPA, PAI-1, and TFPI. Both EVLA and CVS resulted in diversified patients' reaction with respect to a direction of postprocedure changes in proinflammatory factors' serum level. Analysis of proportions showed that the groups differed remarkably in case of ICAM-1 and ET-1, the level of which declined in a higher fraction of patients treated endovenously. Our findings indicate that EVLA preserves better than CVS the functionality of vascular endothelium and modulates better both local and systemic profile of proinflammatory mediators.